Rehabilitative Exercise Strategies for Urinary Incontinence After TURP: A Quasi-Experimental Evaluation of Kegel and Bridging Techniques - Haeruman, Haeruman; Nursanti, Irna; Irawati, Diana (STIKep PPNI Jawa Barat, 2025)
Background: Urinary incontinence (UI) is a common issue following Transurethral Resection of the Prostate (TURP). Pelvic Floor Muscle Training (PFMT), including Kegel and Bridging exercises, is a promising non-pharmacological intervention for managing UI. Objective: This study aimed to evaluate the effectiveness of Pelvic Floor Muscle Training, combining Kegel and Bridging exercises, in reducing urinary incontinence among post-TURP patients, and to identify factors associated with UI severity. Methods: A quasi-experimental pre-posttest design was employed involving 44 male patients who had undergone TURP. Participants were allocated into an intervention group (n = 22), which received six sessions of PFMT over three weeks, and a control group (n = 22), which received standard care. UI severity was measured using the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) before and after the intervention. Data were analyzed using paired t-tests and regression analysis. Results: The intervention group demonstrated a significant reduction in UI scores from 15.50 (SD = 2.50) to 7.41 (SD = 4.12) (p = 0.0001), whereas the control group exhibited only minor improvement. Regression analysis identified age and body mass index (BMI) as significant predictors of UI severity (p = 0.037 and p = 0.041, respectively). Conclusion: Pelvic Floor Muscle Training effectively decreases urinary incontinence severity following TURP surgery. Integrating PFMT into routine postoperative nursing care may enhance patient outcomes and facilitate recovery. Future research should explore long-term adherence and outcomes associated with PFMT in diverse patient populations.